The Development of Building Information Modelling (BIM) Performance Model for the Malaysian Construction Industry - Robin, Rolyselra Orbintang; Yahya, Mohd Yamani (International Journal of Sustainable Construction Engineering and Technology, 2023)
The concept of Building Information Modelling (BIM) has attracted greater attention in the Malaysian construction industry since its introduction in 2007. Several projects in Malaysia such as Pusat Kanser Negara and Convocation Hall, UTHM have adopted this concept. One of the benefits of BIM is the projection of a 3D image of the proposed building, which allows stakeholders to get a better idea of the actual building. BIM also improves the planning and design process of the project and thus the quality of the actual building. These advantages of the BIM concept are crucial for the success of the project. Despite the implementation and benefits of BIM, there are still uncertainties about the actual performance of organisations using BIM. This is because there are no evaluation tools or models in Malaysia that can evaluate BIM performance of BIM. Therefore, this study aims to develop a performance model for the implementation of BIM in the Malaysian construction industry. In this study, the AHP technique was used to collect data. The AHP results have successfully assigned weights to all BIM performance metrics. The consensus value also exceeds 50%, which confirms that the experts' agreement on the weighting of the metrics is acceptable. In conclusion, the proposed and developed BIM performance model could be useful to practitioners, especially the government and CIDB, in evaluating the performance of BIM organisations in the Malaysian construction industry. These measurement results could be a basis for future improvements for BIM organisations.